Determinants of Dengue Prevalence: Aedes Density and Environmental Factors in Johor, Malaysia - Alias, Azwani; Harun, Siti Norliyana; Feisal, Nur Azalina Suzianti; Abd Razak, Mohd Khairudin; Md Noor , Noorashikin; Wee, Hin Boo (Majalah Kesehatan Indonesia, 2025)
Dengue is a common tropical mosquito-borne viral disease that is affected by environmental factors such as rainfall, temperature, and urbanization. This study investigates the relationship of the environmental factors with the distribution of Aedes mosquitoes on dengue transmission in areas identified as suburban and rural in the Kluang district, Johor. Weekly ovitrap surveys were conducted at 20 study sites over four consecutive weeks, with traps retrieved and replaced every seven days. Concurrently, temperature and humidity readings were recorded three times daily to assess their relationship with Aedes mosquito populations. The results indicate a significantly higher Aedes mosquito populations and dengue incidence in the suburban area (Taman Sri Kluang) compared to the rural area (Kampung Palembang). Higher temperatures and lower humidity were strongly associated with increased mosquito abundance and dengue prevalence. Statistical analysis were conducted using R version 4.4.3. The results confirm significant differences in Aedes density and environmental conditions between the two study areas. These findings underscore the need for targeted vector control interventions, climate-adaptive public health strategies, and enhanced dengue surveillance in high-risk areas. Public health intervention should include enhanced vector control in suburban areas, such as frequent larvicidal treatments and improved drainage management. In rural areas, pre-emptive source reduction before peak rainy periods and promotion of covered water storage systems can help minimize mosquito breeding. Additionally, climate-based early warning systems should be integrated into vector surveillance programs to predict and mitigate dengue outbreaks effectively. Community engagement through education campaigns and neighbourhood clean-ups should also be prioritized to sustain long-term dengue prevention efforts. The findings contribute to a better understanding of how climate variability affects mosquito populations, emphasizing the importance of integrating environmental monitoring into dengue prevention programs. Future research should explore the long-term implications of climate change on dengue transmission dynamics.